Combined drying of Nopal pads (Opuntia ficus‐indica): optimization of osmotic dehydration as a pretreatment before hot air drying - Rodriguez, Anabel; Sancho, Ana Maria; Barrio, Yanina Ximena; Rosito, Pablo; Gozzi, Marta Sofía (Wiley, 2019)
The aim of this work was to optimize the osmotic dehydration (OD) as a pretreatment before hot air drying (HAD) in Nopal pads. A Box–Behnken experimental design was used to optimize the OD conditions with respect to physicochemical and chromatic parameters, and mechanical properties of Nopal pads. Factors studied were: Three concentrations of sucrose (30, 40, and 50°Brix), calcium lactate (1, 2, and3%), and immersion time (1.5, 2.5, and 3.5 hr). Results showed that sucrose concentration and immersion time were the variables with higher influence. Quality properties mentioned before and the final mineral content of the dried samples (at 60°C for 48 hr) were analyzed. The combined drying (OD + HAD) reduced the moisture content in the range of 23% to 30% compared to HAD alone. It was found that the optimization of OD allowed preserving the quality properties, being a good alternative to give an added value for dried Nopal pads